A sensorial No Man's Land: corporeality and the Western Front during the First World War. (2nd September 2019) - Leonard, Matthew
ABSTRACT: During the First World War in France and Belgium life on the Western Front was predominantly lived below the surface. The proliferation of hitherto unimaginably powerful weaponry rendered surface existence untenable. This retreat into the earth necessitated a complete revision of soldiers' somatic engagement with their immediate environment. In my work as an archeologist of modern conflict landscapes, I have devised a methodology which combines archeological exploration with participant sensation or "sensory ethnography" to interrogate these complex, ambiguous and often dangerous subterranean places. In this article I show that as the war destroyed it also created new realities in which the senses were forced to work together like never before under the pressures of industrialized warfare. My work suggests how a holistic investigation (grounded in sensorality) of particular modern conflict landscapes can take the form of an ethnographic archeology, or an ethnography of the dead, demonstrating the potential for archeology and anthropology to work together in the increasingly interdisciplinary field of modern conflict studies.